Moving the Goalposts for Blood Pressure — Time to Act - Nelson, Mark R (The New England journal of medicine, 2021)
We often lament the lack of confirmatory studies that can either reassure us all that the previous evidence for a trialed intervention is robust or indicate that the evidence is questionable. Zhang and colleagues have conducted such a study — the STEP trial 1 — which in essence investigates the veracity of the findings of the previous trial SPRINT, 2 but in an older cohort and in China, a country with a considerable burden of high blood pressure and stroke. The investigators have demonstrated impressive organizational skills in completing recruitment for such a large multicenter trial within a calendar year. As in . . .